2007
DOI: 10.3391/ai.2007.2.3.2
|View full text |Cite
|
Sign up to set email alerts
|

Alien Crustacean Decapods from the Aegean Coast of Turkey

Abstract: Rhithropanopeus harrisii (Gould, 1841) is an estuarine crab native to the East Coast of North America. This species has invaded both the West Coast of the United States and several European countries since the late 1800s where it has reportedly altered native ecosystems. This crab can tolerate a broad range of salinities and temperatures, which probably contributes to its success as an invader. In 1969, five specimens of R. harrisii were recorded in Panama, but subsequent surveys suggest it was not established… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…The first record of A. roseus in the Mediterranean was reported from Israel and thereafter the species expanded to Lebanon, Syria, Turkey, Greece, Egypt and Cyprus (for details see Crocetta et al, 2015a). In the southern Aegean Sea, the species was first reported from the coasts of Datça Peninsula, Turkey (Yokes et al, 2007) then Rodos Island, Greece (Corsini-Foka & Pancucci-Papadopoulou, 2010) where it is common (ELNAIS: Zenetos et al, 2015), and recently Gökova Bay, Turkey (Ateş et al, 2016).…”
Section: First Record Of Gaper (Champsodon Capensis Regan 1908) In Tmentioning
confidence: 99%
“…The first record of A. roseus in the Mediterranean was reported from Israel and thereafter the species expanded to Lebanon, Syria, Turkey, Greece, Egypt and Cyprus (for details see Crocetta et al, 2015a). In the southern Aegean Sea, the species was first reported from the coasts of Datça Peninsula, Turkey (Yokes et al, 2007) then Rodos Island, Greece (Corsini-Foka & Pancucci-Papadopoulou, 2010) where it is common (ELNAIS: Zenetos et al, 2015), and recently Gökova Bay, Turkey (Ateş et al, 2016).…”
Section: First Record Of Gaper (Champsodon Capensis Regan 1908) In Tmentioning
confidence: 99%
“…The Lessepsian immigrant Portunus segnis (Forskål, 1775) was reported from the Aegean (Yokeş et al, 2007) and Levantine (Gruvel, 1928) coasts of Turkey. Altuğ et al (2011) reported this species from the Sea of Marmara.…”
Section: Evaluation Of Speciesmentioning
confidence: 99%
“…Until December 2005, alien species in the Mediterranean was estimated to be 745 species (Zenetos et al 2005). Species richness in the Mediterranean has been changing with the increasing number of introduced lessepsian species , Ozcan .et al 2006, Yokes et al 2007, Galil 2005, Yokes and Galil 2006, Horton et al 2004, Galil 2004, Cinar and Altug 2007.…”
mentioning
confidence: 99%